Development Strategy of a Selected International Trade Intermediary - Kovalenko, Mykola; Hinčica, Vít; Mervart, Michal, 1977-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The given problem which is being observed in this bachelor thesis is a drafting of the development strategy for a specific enterprise on the basis of current trends in the market. The reader will find the detailed description of the tasks of indirect exporting, including its advantages and disadvantages in this study. The most important part of the work the author considers are the recommendations leading to the achievement of profit in the given area of a business. The mentioned opinions are based on scientific knowledge, recognized worldwide level experts, whereas the analysis is carried out from the official statistical sources and the scientific literature. The defined goals, which the author assigns, are the following:1. To formulate a workable development strategy for the company KONIK EXIM TRADING based on profit2. To propose solutions to the problems the enterprise was facing during a certain period of time.
Vedoucí práce: Vít Hinčica
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses